2019
DOI: 10.20950/1678-2305.2019.45.1.252
|View full text |Cite
|
Sign up to set email alerts
|

PROBIOTIC Bacillus subtilis AND Lactobacillus plantarum IN DIET OF NILE TILAPIA

Abstract: The aim of this study was to evaluate the effects of a probiotic, composed of Bacillus subtilis and Lactobacillus plantarum in Nile tilapia fry during the sex reversal phase under stress conditions caused by high stocking density. This experiment was conducted in the Fisheries Institute of São Paulo. The experiment design was completely randomized with four treatments: 1) probiotic added feed, 2) probiotic added to water, 3) probiotic added to feed and water and 4) control diet; with three replicates. The vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…The greater activity of maltase in Nile tilapia occurs in the gastric loop region so that most glucose release occurs in the medial portion of the intestine (Tengjaroenkul et al 2000). The distribution of maltase activity in the middle intestine of Nile tilapia is like other studies involving amylase activity that hydrolyzes starch into maltose or glucose (Evans 1998;Stevens and Hume 2004) which corroborates to the present work.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The greater activity of maltase in Nile tilapia occurs in the gastric loop region so that most glucose release occurs in the medial portion of the intestine (Tengjaroenkul et al 2000). The distribution of maltase activity in the middle intestine of Nile tilapia is like other studies involving amylase activity that hydrolyzes starch into maltose or glucose (Evans 1998;Stevens and Hume 2004) which corroborates to the present work.…”
Section: Discussionsupporting
confidence: 90%
“…In a previous study, the inclusion of probiotics B. subtilis and L. plantarum in diets for Nile tilapia fry, during the sex reversal phase, modified the fish intestinal microbiota (Guimarães et al 2019). Therefore, the aim of this research was to evaluate the effects of feeding Nile tilapia (O. niloticus) with a diet containing 0.08% of a commercial probiotic AQUA-PHOTO ® [L. plantarum (1.51 × 10 6 CFU.g −1 ) and B. subtilis (1.34 × 10 7 CFU.g −1 )] on digestive enzymes' activity and gut microbiome profile.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, the time of probiotic administration is an important factor to promote the beneficial effects, such as the production of digestive enzymes, inhibition of pathogenic bacteria, among others [35]. In this study, we verified significant difference in biomass between the 63rd and 84th days of the experiment.…”
Section: Discussionsupporting
confidence: 64%
“…also observed higher survival of tilapia and digestive enzymes production, using a combination of different species of Bacillus at concentrations of 10 7 CFU/g and 10 8 CFU/g for a period of two weeks Dawood et al (2020a),Tan et al (2019). andAddo et al (2017a) also reported similar results administering probiotics at concentration in the range 10 6 -10 8 CFU/g, even though the treatment was prolonged for about 2 months in these studies Guimarães et al (2019. andAyyat et al (2014) included in their assays Lb.…”
supporting
confidence: 61%